Small intestine anastomosis by full thickness, single layer and interrupted suture technique: results of a comparative study - Nemma, Shobhit K.; Singh, Sarbjeet; Rana, Amritpal Singh; Kapoor, Rohit; Bansal, Puneet (International Surgery Journal, 2019)
Background: Since the dawn of surgery intestinal anastomosis has remained a controversial topic in respect to suture material, anastomotic technique, distance between stitches and borders. Technique of anastomosis is an important determinant in process of anastomosis healing. Despite a large amount of work done on anastomosis techniques, a clear superiority of one technique over another has not been established. Methods: Patients of ileostomy reporting to surgery department for stoma closure were used for study. 80 patients of ileostomy reporting for stoma closure were used as material for the study and randomized in two groups. In single layer group, using 3-0 silk suture, we performed small intestine anastomosis applying single layer of interrupted sutures taking full thickness bite. In double layer group, anastomosis was performed anastomosis by applying first layer of full thickness sutures and second layer of seromuscular sutures. The results were compared in terms of operative time, post operative complications, mortality, hospital stay and cost of the suture material. Results: The mean age of the patients was 33.55 yr in group A (single layer) and 35.85 yr in group B (double layer). Total 7 patients developed anastomotic leak. 5 (12.5%) patients were with double layer anastomosis and 2 (5%) patients were in single layer group. The difference in anastomosis leak in two groups was statistically insignificant (p = 0.232). The mean duration of whole procedure in group A (single layer) was 52.5min and 71.5min in group B (double layer). The difference in mean duration of the procedure was found to statistically significant (P = 0.00). Conclusions: We concluded the single layer technique to be a safe, efficient and more cost effective as compared to double layer technique.